Ownership patterns and control of top 100 Malaysian listed companies - Che Ahmad, Ayoib (EDP Sciences, 2017)
The incentive of this study stems from the significance of protecting minority shareholders’ rights.It analyses the most dominant ownership structure practices within listed firms in Bursa Malaysia (BM), in which controlling shareholders (CSs) hold control on many firms despite relatively small portion of investment. Malaysian firms are characterised by high levels of concentrated ownership with families owning more than 70% of the listed firms in BM [9].This study finds that the separation between cash flow rights (real investment) and control rights (voting rights) for Top 100 Malaysian listed firms is accomplished through pyramidal ownership and golden share arrangements.Hence, the divergence between cash flow rights (CFRs) and voting rights (VRs) exacerbates Type II Agency problem.This study calls for future studies in the area of accounting and finance to introduce and operationalise new measurement of Type II Agency Cost in order to better understand the agency conflicts within this unique market.It also better explains the state of the minority shareholders in the BM.